2017
DOI: 10.1021/acs.inorgchem.7b02170
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Characterization of AM2V2O11 (A = Ba, Sr, Pb; M = Nb, Ta) Vanadates with Centrosymmetric and Noncentrosymmetric Structures

Abstract: Five isomorphous AMVO vanadates of niobium and tantalum, namely, BaNbVO, BaTaVO, SrNbVO, SrTaVO, and PbTaVO, were prepared by solid-state reactions and structurally characterized by single-crystal and powder X-ray diffraction techniques. Barium and strontium compounds, respectively, have centrosymmetric and noncentrosymmetric types of layered structure, wherein [MVO] anionic layers are interleaved with A cations. Both types of layered structure are found for lead compound. The strontium and lead compounds are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…Anomalies in Born charges of strontium (lead), tantalum, and structurally related oxygen atoms are similar to some of layered perovskite-type ferroelectrics, while vanadium species are inactive in the formation of the polar structure of STVO and PTVO. Calculated band gaps are found to be consistent with experimental data of ref ( 11 ), although these are relatively far from the desirable 1.3–1.6 eV for photovoltaic applications. This implies that careful doping of parental matrices with proper cations is a suitable approach to narrow the band gaps and may pave the way for further studies of bulk photovoltaic effects of tuned material.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Anomalies in Born charges of strontium (lead), tantalum, and structurally related oxygen atoms are similar to some of layered perovskite-type ferroelectrics, while vanadium species are inactive in the formation of the polar structure of STVO and PTVO. Calculated band gaps are found to be consistent with experimental data of ref ( 11 ), although these are relatively far from the desirable 1.3–1.6 eV for photovoltaic applications. This implies that careful doping of parental matrices with proper cations is a suitable approach to narrow the band gaps and may pave the way for further studies of bulk photovoltaic effects of tuned material.…”
Section: Discussionsupporting
confidence: 78%
“…The subtle structural distortions are intrinsic for A Ta 2 V 2 O 11 (A = Sr or Pb) due to polarized Ta–O and V–O bonds that stabilize the polar lattice of monoclinic symmetry for both compounds, in contrast to previous studies, as revealed by high-resolution X-ray diffraction. 6 , 11 , 13 The chemical type of the counter-cation, Sr or Pb in the present case, has further influence on the overall crystal packing via the local oxygen environment built up around them in a specific fashion. The atomistic view projected on studied compounds helps us to formulate several outcomes: (i) Pb 6s 2 participates in the construction of the top of valence band zone in contrast to the Sr analogue; (ii) the AMM approach allows one to detect residual V Pb interactions induced by the anisotropic behavior of the lone pair in the interior of Pb metallic centers.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Many metal vanadates featuring isolated VO 4 tetrahedron are able to display large SHG effects, such as Li 3 VO 4 (6 × KDP), LiRb 2 VO 4 (5 × KDP) and SrTa 2 V 2 O 11 (0.5 × LiNbO 3 ). [30][31][32] Interestingly, K 3 V 5 O 14 (100 × α-SiO 2 ) contains a 2D [V 5 O 14 ] 3 ˉ layer involving both VO 4 and VO 5 groups. 33 Moreover, introducing the V 5+ cation into metal iodate might achieve large SHG effects, hence the vanadyl iodates are an ideal materials class for the exploration of SHG crystals.…”
Section: Introductionmentioning
confidence: 99%